Analisis Pola Pengembangan Paragraf dalam Karangan Narasi Siswa Kelas VIII SMP Negeri 3 Colomadu - Dewi, Suci Meiyanti Fransiska; , Dra. Atiqa Sabardila, M. Hum (2017)
This study aimed to (1) describe the pattern of development of the paragraphs in the narrative text eighth grade tudents of SMP Negeri 3 Colomadu, and (2) identify markers circuited between sentences used in the development of narrative aragraphs of the essay students. The data used in this study is the composition students of SMP Negeri 3 Colomadu. The data collection technique used is the technique of cumentation. Data analysis methods are applied in this research is the method followed by the engineering agih for direct elements, expansion, and dressing. The results of this study are as follows. (A) Based on the analysis of patterns development of 42 paragraphs, namely, (1) the development pattern of paragraphs climax and anticlimax fifth paragraph, (2) the pattern of paragraph development standpoint 12 paragraph, (3) the development pattern of paragraphs comparisons and contradictions second paragraph, (4) the development pattern of paragraphs example 3 paragraph, (5) the type of pattern paragraph development process 7 paragraph, (6) the type of development pattern paragraphs causal sixth paragraph, (7) the development pattern paragraph special general third paragraph, (8) the development pattern of paragraphs classification 3 paragraphs, and (9) the development pattern definition paragraph 2 paragraphs. (B) Based on the analysis of the type of marker circuit between sentences of 15 paragraphs, namely (1) the marker circuited appointment of two paragraphs, (2) a marker circuited replacement fifth paragraph, (3) a marker circuit coupling 4 paragraphs, and (4) a marker circuited relationship lexical 4 paragraphs.